THE CHALLENGES OF SOCIAL WORKERS IN THE AREA OF EDUCATION, SPORTS AND LEISURE (Fiep Bulletin - online, 2019)
In strategically and tactically studying the class struggle, we must ask ourselves what does the concrete struggleagainst the capitalist system mean in the current conjuncture? What system is this? What imposed mankind? How do youmaintain your survival? How was the regulation of Physical Education important for the struggle of these professionals? Howimportant is the CONFEF / CREF system to ensure the labor market and ensure security in serving the society? Education ascultural policy for the broad masses is the order of the day. It is up to us to fulfill our tasks as organic intellectuals and culturalactivists for the construction of socialism because, as the studies of Marx and Engels on French Socialism, German Philosophyand the English Economy show, this will not be the result of change of beliefs in a society. Through the awareness of individuals asthe product of contact with them, will fulfill the social worker, the role of agent of change.